Evaluating The Effectiveness of The Binjai Cerdas Program for Baznas Beneficiaries in Binjai City - Salwa Apriliza; Juliana Nasution; Rahmat Daim Harahap (Islamiconomic : Jurnal Ekonomi Islam, 2026)
This study aims to analyze the success rate of the Binjai Cerdas Program organized by the National Zakat Agency (BAZNAS) of Binjai City. Previous studies have mainly focused on the effectiveness of zakat distribution in general, while evaluations of local zakat education programs remain limited. This study employs a quantitative, descriptive method. The sample comprised 100 respondents who received assistance from the Binjai Cerdas Program and were purposively selected. Data were collected via questionnaires and analyzed using IBM SPSS Statistics, including validity and reliability tests and descriptive analyses. The results indicate that all research instruments are valid and reliable, with a Cronbach’s Alpha value of 0.955. Descriptive analysis shows that the program’s effectiveness achieved 82.6%, target accuracy 84.6%, educational impact 86.6%, and program sustainability 90.2%, all of which fall into the “highly successful” category. The findings indicate that the Binjai Cerdas Program has been implemented effectively, is well-targeted, positively impacts beneficiaries’ education, and demonstrates good sustainability. The novelty of this study lies in integrating effectiveness, targeting accuracy, educational impact, and sustainability into a single evaluation framework. Theoretically, this study contributes to the Islamic social finance literature by highlighting the role of educational zakat in supporting human capital development. In practice, the findings provide BAZNAS with insights into improving the effectiveness and sustainability of educational assistance programs.